Compact silicon-based optrode with integrated laser diode chips, SU-8 waveguides and platinum electrodes for optogenetic applications. (25th April 2017) - Schwaerzle, M; Paul, O; Ruther, P
Abstract: We report on a compact optrode, i.e. a MEMS-based, invasive, bidirectional neural interface allowing to control neural activity using light while neural signals are recorded nearby. The optrode consists of a silicon (Si) base carrying two pairs of bare laser diodes (LDs) emitting at 650 nm and of two 8 mm-long, 250 µ m-wide and down to 50 µ m-thick shanks extending from the base. Each LD is efficiently coupled to one of four 15 or 20 µ m-wide and 13 µ m-high SU-8 waveguides (WGs) running in pairs along the shanks. In addition, each shank comprises four 20 µ m-diameter platinum electrodes for neural recording near the WG end facets. After encapsulation of the LDs with a Si cover chip blocking stray light and protecting the LDs from the harsh environment to which the probe is destined, the compact base measures only 4 × 4 × 0.43 mm 3 . The time averaged radiant emittance at the WG end facet is 96.9 mW mm −2 for an LD current of 35 mA at a duty cycle of 5%. The absolute electrode impedance at 1 kHz is 1.54 ± 0.06 MΩ. Using infrared thermography, the temperature increase of the probe during LD operation was determined to be about 1 K under neuroscientifically relevant operating conditions.